Prevention of Mother-to-Child Transmission of HIV data completeness and accuracy assessment in health facilities of the Nkangala District - Motlatso G. Mlambo; Karl Peltzer; Annariina Koivu (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2014)
Background: Even though significant progress has been made in the roll-out and quality of the prevention of mother-to-child transmission of HIV (PMTCT) services in South Africa, the quality of patient data recording remains a challenge. Objectives: To assess PMTCT data completeness and accuracy at primary healthcare level to district level in order to assist with the improvement of the PMTCT data recording.